2022
DOI: 10.1128/spectrum.03282-22
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever Virus MGF110-7L Induces Host Cell Translation Suppression and Stress Granule Formation by Activating the PERK/PKR-eIF2α Pathway

Abstract: African swine fever (ASF) has become a socioeconomic burden and a threat to food security and biodiversity, but no commercial vaccines or antivirals are available currently. Understanding the viral strategies to subvert the host translation machinery during ASF virus (ASFV) infection could potentially lead to new vaccines and antiviral therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…As shown in Table 3, 3 out of the 8 genes have been previously identifed as involving immune modulation of host responses. MGF 110-7L induces host cell translation suppression and stress granule formation by activating the PERK/PKR-eIF2 alpha pathway [57]. MGF360-10L has been implicated in the modulation of the type I interferon (IFN) response and associated with the virulence of the virus [58].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 3, 3 out of the 8 genes have been previously identifed as involving immune modulation of host responses. MGF 110-7L induces host cell translation suppression and stress granule formation by activating the PERK/PKR-eIF2 alpha pathway [57]. MGF360-10L has been implicated in the modulation of the type I interferon (IFN) response and associated with the virulence of the virus [58].…”
Section: Discussionmentioning
confidence: 99%
“…The MGF110-7L is implicated in subverting the host protein synthesis machinery, inducing phosphorylation of eIF2α through protein kinase R (PKR) and PKR-like endoplasmic reticulum (ER) kinase (PERK). This process was found to be essential for host translation repression and stress granule (SG) formation [ 57 ]. Certain members of the MGF360 family have been identified as essential for replication in pigs, ticks, and macrophages [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that the ASFV gene MGF110-7L was downregulated significantly in the transcriptome of ASFV-GS-Δ18R/NL/UK but not in that of ASFV-GS. ASFV MGF110-7L has been reported to trigger stress granule (SG) formation and inhibit host cell translation by inducing phosphorylation of the α subunit of eukaryotic initiation factor 2 (eIF2α) ( 29 ). This process may play an important role in the virulence of ASFV in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the downregulation of MGF110-7L and three deleted genes remains unclear. Given that MGF110-7L and DP71L are found to be functionally linked to eIF2α ( 29 , 30 ), it is reasonable to speculate that altering one gene may have an impact on the other. In addition, these genes might have other, as-yet-unidentified, functions.…”
Section: Discussionmentioning
confidence: 99%